2011
DOI: 10.1371/journal.pgen.1002264
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association for Renal Traits among Participants of African Ancestry Reveals New Loci for Renal Function

Abstract: Chronic kidney disease (CKD) is an increasing global public health concern, particularly among populations of African ancestry. We performed an interrogation of known renal loci, genome-wide association (GWA), and IBC candidate-gene SNP association analyses in African Americans from the CARe Renal Consortium. In up to 8,110 participants, we performed meta-analyses of GWA and IBC array data for estimated glomerular filtration rate (eGFR), CKD (eGFR <60 mL/min/1.73 m2), urinary albumin-to-creatinine ratio (UACR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 41 publications
3
96
0
Order By: Relevance
“…Although recent genome-wide association studies (GWASs) have implicated several loci and genes in renal function or predisposition to CKD or ESRD in Caucasian7–11 or African American12 13 populations, or in renal function related traits in East Asian populations,14 the genes that contribute to genetic susceptibility to CKD in Japanese individuals remain to be identified definitively.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent genome-wide association studies (GWASs) have implicated several loci and genes in renal function or predisposition to CKD or ESRD in Caucasian7–11 or African American12 13 populations, or in renal function related traits in East Asian populations,14 the genes that contribute to genetic susceptibility to CKD in Japanese individuals remain to be identified definitively.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent results in African and European ancestry populations is reassuring and smaller haplotype blocks in those of African ancestry may facilitate detection of causal SNPs. 106 Perhaps surprisingly, although several major eGFRassociated loci were found to be associated with development of CKD (e.g. UMOD, PRKAG2, ANXA9, DAB2, DACH1, and STC1), only UMOD was nominally associated with ESRD.…”
Section: Alpha-actinin 4 (Actn4) -Fsgs (Ad)mentioning
confidence: 96%
“…A recent genome-wide association study suggested a potential link between AGS8/FNDC1 and urinary albumin-tocreatinine ratio in African Americans from the CARe Renal Consortium (Liu et al, 2011). However, morpholino knockdown of AGS8/FNDC1 in zebrafish did not support a role for this protein during renal development or dysfunction (Liu et al, 2011).…”
Section: Group III Ags Proteinsmentioning
confidence: 99%